Provision in insurance companies according to ifrs 4 and current practice of turkish insurance companies - Erol, Duygu (My University, 2007)
SİGORTA ŞİRKETLERİNDEKİ KARŞILIKLARIN UFRS 4’ E GÖRE İNCELENMESİ VE TÜRK SİGORTA ŞİRKETLERİNİN GÜNÜMÜZDEKİ MUHASEBE UYGULAMALARI Günümüzde artan küreselleşme ve rekabet olgusu ile birlikte, şirketler finansal raporlama yaparken daha açık, anlaşılabilir, yorumlanabilir, karşılaştırılabilir raporlamaya ihtiyaç duymuşlardır. Farklı ülkelerde farklı kurallara göre raporlamanın yapılması finansal raporların uyumlaştırılması ihtiyacını doğurmuştur. Amerikan Genel Kabul Görmüş Muhasebe İlkeleri ile Uluslar arası Muhasebe Standartlarının yakınsama çalışmalarının artması, AB üyesi ülkelerde borsada işlem gören şirketlerin konsolide finansal tablolarını UMS’ ye göre düzenlenmelerinin zorunlu hale gelmesi, diğer ülkeleri de UMS’ ye uygun raporlama çalışmaları yapmaya itmiştir. Uluslar arası Muhasebe Standartları Kurulu sigorta sözleşmeleri ile ilgili düzenlemeleri iki aşamada yapmaktadır. UFRS 4 bu çalışmanın birinci aşamasını içermektedir. İkinci aşama ise 2009 yılından itibaren yürürlüğe girecektir. Sigorta şirketlerinin finansal tablolarındaki en önemli kalem sigorta yükümlülükleridir. Bu yüzden, zamanı ve miktarı belli olmayan yükümlülükler demek olan “karşılıklar” sigorta şirketleri için çok önemlidir. Türk sigortacılık terminolojisine has olan “teknik karşılıklar” terimi sigorta şirketlerinin esas faaliyetleri nedeniyle ortaya çıkan karşılıklar için kullanılır. UFRS 4’te kazanılan primlerin muhasebe kayıtlarına alınmasında(tanınmasında) UMS 18 Hasılat’ın gerektirdiğinden farklı bir uygulama mevcuttur.. Bu tezde Türk Sigorta şirketlerinin finansal raporlama sistemi ele alınmış, sigorta şirketleri için en önemli kalemlerden biri olan teknik karşılıklar detaylı bir şekilde incelenmiştir.Sigorta şirketlerinin UFRS 4’e göre raporlama yapmaları halinde neleri değiştirmeleri gerektiği, nerelerde sorunlar yaşayacakları açıklanmaya çalışılmıştır. Ayrıca 2004 yılında değişen sigortacılık tek düzen hesap planının teknik karşılıkları nasıl etkilediğini göstermek amacıyla teknik karşılıkların analizi yapılmıştır.

PROVISIONS IN INSURANCE COMPANIES ACCORDING TO IFRS 4 AND CURRENT PRACTICE OF TURKISH INSURANCE COMPANIES Companies need fairer, more understandable, more comparable financial reporting because of the increase in globalization and competition. Different countries use different financial reporting systems, so there is a need to converge these financial statements. EU adoption to IAS in 2005 and IASB-FASB convergence process makes an enormous effect to other countries to converge their financial reporting to IFRS/ IAS. IFRS 4 represents the first phase of the project of insurance companies; draft of Phase II will be in effect by 2009. Liabilities of insurance companies are the significant items in financial statements of insurance companies. Therefore, provisions as liabilities with uncertain timing and amount are very important for this industry. In Turkish insurance terminology, provisions for operating activities of insurance companies are called “technical provisions” which is unique for Turkey. CONTENT Pages List of TablesIV List of Figures V Abbreviations VI INTRODUCTION 1 1. BASIC CONCEPTS 4 1.1. Insurance and Relevant Terminology 4 1.2. Operating Activities of Insurance Companies12 1.3. Characteristics of Insurance Business in View Of Financial Reporting15 1.3.1 Life Insurance Companies’ Balance Sheets and Recent Trends17 1.3.2. Property and Casualty Insurance Balance Sheet18 2. FINANCIAL REPORTING DEVELOPMENTS FOR INSURANCE COMPANIES IN TURKEY20 2.1. Historical Developments of Financial Reporting in Turkey and in the World20 2.1.1. Turkish Accounting Standards22 2.1.2. International Accounting Standards24 2.1.3. Turkish Insurance Accounting26 2.1.4 Insurance Accounting in International Financial Reporting Standards29 2.2. Uniform Chart of Accounts for Insurance Operating in Turkey Promulgated by the Treasury34 2.2.1. Balance Sheet and Non Balance Sheet Accounts34 2.2.2. Income Statements36 2.2.3. Special Accounts for Insurance Companies38 2.3. Other Regulations Regarding Financial Reporting for Insurance Companies in Turkey.40 3. PRECAUTIONS FOR POSSIBLE FUTURE LOSSES45 3.1 Provisions in Insurance Accounting46 3.1.1. Provisions in Turkish Insurance Accounting46 3.1.2. Provisions Based on IFRS47 3.2. Technical Provisions Used in Insurance Accounting48 3.2.1. Unearned Premium Provisions and Unexpired Risk Provisions 48 3.2.1.1. Unearned Premium Provisions and Unexpired Risk Provisions in Turkey49 3.2.1.2. Unearned Premium Provisions according to IFRS53 3.2.2. Outstanding Loss Provision54 3.2.2.1. Outstanding Loss Provisions used in Turkish Insurance Accounting55 3.2.2.2. Outstanding loss provisions used in IFRS59 3.2.3. Equalization Reserves65 3.2.3.1. Equalization Reserves according to Turkish Insurance Accounting66 3.2.3.2. Equalization Reserves based on IFRS69 3.2.4. Mathematical Reserves71 3.2.4.1. Actuarial Mathematical Reserves71 3.2.4.2. Bonus Reserves72 4- PRESENT PRACTICE OF FINANCIAL REPORTING STANDARDS IN TURKEY73 4.1. The Changes that will occur if ISE Listed Insurance Companies Complied with IFRS 475 4.2 Key Issues Arising From the Insurance Accounting Standards82 4.3. AVIVA Insurance Company and Its Convergence Process to IFRS 4 85 4.4. Analysis of Insurance Technical Provisions using Consolidated Balance Sheets of Turkish Insurance Companies92 4.4.1. Financial Ratios used for Analysis of Insurance Companies 94 4.4.1.1. Technical Provisions per annum96 4.4.1.2. Technical Provisions/ Increase in Premiums 98 4.4.1.3. Technical Provisions / Total Liabilities 99 4.4.1.4. (Technical Provisions + Shareholder’s Equity)/ Total Liabilities 100 4.4.1.5. Shareholder’s Equity/ Technical Provisions 101 4.4.1.6. Loss/ Premium Ratio 102 4.4.2. Development of Technical Profit 104 5. CONCLUSION 108 6. APPENDIX 111 6. REFERENCES 118
Keywords: Muhasebe; Sigorta Şirketleri_Muhasebe; Sigortacılık_Muhasebe